Analyzing Maternal Mortality in Nigeria: A Qualitative Study Approach using the Three Phases of Delay - GinaMarie Piane; Precious Chidozie Azubuike (Journal of Health Promotion and Behavior, 2023)
Background:  Nigeria has a Maternal Mortality Ratio of 814 per 100,000 births. Only 30% of births in Nigeria occur in health facilities. A proven method to prevent maternal deaths is to provide emergency obstetric care and promote hospital birth. Application of the Three Phases of Delay Model to hospital births in Nigeria directed a community needs assessment and may influence local and regional health promotion efforts with the goal of preventing maternal deaths. This study aimed to analyze maternal deaths in Nigeria, employing a qualitative approach with the Three Phases of Delay model.Subjects and Method: This was a qualitative study grounded in theory research that employed focus groups and key informant interviews in Cross River State, Nigeria. A stratified random sampling of local government areas was followed by a random selection of wards and a purposive selection of key informants and focus group participants. In total 26 key informants and 100 focus group, discussion participants were selected across the wards in accordance with local customs. All responses were recorded digitally and transcribed verbatim. All key informant interviews and all but two focus groups were conducted in English. Data were collected in December 2016, over a four-week period. The transcripts were analyzed using Atlas TI to designate codes and to compile quotes by theme.Results:  Application of the Three Phases of Delay Model to hospital births in Cross River State, Nigeria found significant points of delay at all levels of the Delay Model. The most prevalent of the delays described by the focus groups and key informants were delays in reaching the point of care and delay in receiving quality care at the health facility.Conclusion:  Identifying the influences on delay can be employed to develop and plan local and regional health promotion efforts with the goal of preventing maternal death.Keywords:  maternal mortality, childbirths, pregnancy, delay model, health facility.Correspondence:Precious Chidozie Azubuike. Department of Public Health, College of Medical Sciences, University of Calabar, PMB 1115, Calabar, Nigeria. Email: azubuikepreciousc@gmail.com. Phone: +234810- 6353021.Journal of Health Promotion and Behavior (2023), 08(01): 22-33DOI: https://doi.org/10.26911/thejhpb.2023.08.01.04